Tools to Reduce Low-Value Care: Lessons From COVID-19 Pandemic; Comment on "Key Factors that Promote Low-Value Care: Views of Experts From the United States, Canada, and the Netherlands" - Luis Corral-Gudino (Kerman University of Medical Sciences, 2022)
Based on a summary of interviews with 18 experts, Verkerk et al defined the seven key factors that promoted lowvalue care, which included system, social, and knowledge factors. During the ongoing coronavirus disease 2019 (COVID-19) pandemic, these key factors have been influential due to the uncertainty of the disease at the beginning of the pandemic. Globally, several measures have been implemented to reduce low-value care practices and promote high-value care for COVID-19 patients. From huge multicenter, non-industry sponsored or multiplatform trials, to the use of social networks sites is an indispensable and effective way to disseminate medical information. Thanks to these measures, we have transformed a scenario of ignorance into an evidence-based medical scenario in less than a year. Verkerk and colleagues' proposed key factors are an excellent framework for characterizing and highlighting the lessons that can be learnt from how we have fought against the pandemic and low-value practices.